2021
DOI: 10.1167/iovs.62.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Low-Moderate Hyperopia Improves Accommodative Function for Some Hyperopic Children During Sustained Near Work

Abstract: PURPOSE. This study investigated whether refractive correction improved accommodative function of hyperopic children while engaged in two sustained near activities. METHODS.Sustained accommodative function of 63 participants (aged 5-10 years) with varying levels of uncorrected hyperopia (>/= +1.00 D and < + 5.00 D spherical equivalent in the least hyperopic eye) was measured using eccentric infrared photorefraction (PowerRef 3; PlusOptix, Germany). Binocular accommodation measures were recorded while participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(61 citation statements)
references
References 49 publications
(56 reference statements)
0
60
0
1
Order By: Relevance
“…A total of 7 studies explained the cutoff thresholds used to define hyperopia. 12,27,33,53,64,69,74 Four (16.0%) studies used the plus-lens test to identify participants with hyperopia. 12,29,66,71 Three out of these 4 studies, further defined hyperopia using the SE.…”
Section: Classification Of Hyperopia and Measurement Toolsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 7 studies explained the cutoff thresholds used to define hyperopia. 12,27,33,53,64,69,74 Four (16.0%) studies used the plus-lens test to identify participants with hyperopia. 12,29,66,71 Three out of these 4 studies, further defined hyperopia using the SE.…”
Section: Classification Of Hyperopia and Measurement Toolsmentioning
confidence: 99%
“…10,27,29,[72][73][74]78 All 4 studies assessing reading speed have reported outcome measures separately; therefore, reading speed was evaluated as a separate domain. 29,53,69,76 Three studies used standardized tests to measure and report reading speed. 29,53,76 Lanc ¸a et al 69 reported the validity of the tool used to assess reading skills and speed.…”
Section: ããããmentioning
confidence: 99%
See 2 more Smart Citations
“…The advent of eye trackers has allowed quantitative estimates of gaze position to be obtained more quickly. Such instruments, particularly those using the displacement of the first‐Purkinje image (PI) (i.e., the separation between the 1st Purkinje image and pupil centre, [PC]) to determine angular units of gaze position in children are being used both in research and clinical practice 2–6 1,7,8 .…”
Section: Introductionmentioning
confidence: 99%